Aplikasi Sistem Untuk Penerbitan Surat Izin Belajar Bagi Warga Negara Asing Yang Akan Menempuh Pendidikan di Indonesia - Dwiky Dwicahyo; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
According to the Global Partnership for Education, Indonesia ranks 55th out of 77 countries in terms of education. The ranking is one factor that attracts foreigners to pursue their education in Indonesia. Moreover, foreign nationals who wish to study in Indonesia must comply with Indonesian laws and regulations, including obtaining a letter of approval for their study permit from the Ministry of Education, Culture, Research, and Technology. This study aimed to improve the quality of service at the Ministry of Education, Culture, Research, and Technology to make it more effective and efficient in issuing study permits for foreign nationals. Schools and foreign nationals no longer need to bring hardcopy documents from their home countries to the Ministry of Education, Culture, Research, and Technology. This research aimed to process the study permit administrative requirements through a web-based application that can be accessed anytime and anywhere. Moreover, it makes it easier for staff to process the issuance of approval letters without having to check through piles of hardcopy documents. The methodology used in designing the Application System was the SDLC waterfall model. The data was collected through interviews and observations with several employees and leaders in the unit responsible for issuing study permits. The results of this research indicated that the study permit issuance application is very effective and efficient for foreign nationals and staff in the issuance process and significantly reduces paper (paperless) use.